The Symbiotic Ideology: Stewardship, Husbandry, and Dominion in Beef Production1. (December 2013) - Ellis, Colter
Abstract Social studies of agriculture tend to overlook the micro and symbolic interactions that structure relationships among agriculturalists, the environment, and animals raised as commodities. In this study, I use ethnographic methods and in‐depth interviews with conventional beef producers to understand their perceptions of the environment and the nonhuman animals they raise. Central themes in this setting are the ethics of stewardship and husbandry. I seek to understand how these values are constructed and used interactionally. I argue that stewardship and husbandry help describe a process of co‐constitution that binds together ranchers, cattle, and the natural environment. The analysis engages actor‐network theory by emphasizing nonhuman activeness and draws from symbolic interaction and cultural sociology to show how people interpret the actions of nonhumans. The findings show that ranchers frame their relationships with cattle and the environment as symbiotic and work to understand the interests of the nonhuman as complementary to production. I introduce the term symbiotic ideology to show the way this approach mystifies power dynamics embedded in the ethic of dominion.